Morpho-anatomical adaptations of Potamogeton polygonus (Potamogetonaceae) to lotic and lentic environments - Makeli Garibotti Lusa; Maria Regina Torres Boeger; Maria Cecília de Chiara Moço; Cleusa Bona (Rodriguésia)
Abstract Aquatic macrophytes show great phenotypic plasticity and are able to occupy environments with different physicochemical conditions. The present study aimed to characterize morphology and anatomical structure of the pondweed, Potamogeton polygonus Cham. & Schltdl., and to identify adaptive modifications of the plant in lotic and lentic environments. Sampling was carried out in Palmas and General Carneiro, Paraná state, southern Brazil. Ten individuals from each locality were collected. Morpho-anatomical characteristics of the roots, stems and leaves were measured. The anatomical structure was analyzed with light microscopy and scanning electron microscopy. Significant morphological and anatomical adaptive differences were observed between plants of the two environments.